Characterization of perchlorate biodegration of sulfur oxidizing enrichment culture - Rasco, Raymund B. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Perchlorate (ClO4-) is a contaminant commonly found in ground water and surface water. Perchlorate is known to be degraded to chlorine using autotrophic bacteria. The use of perchlorate reducing bacteria (PRB) has been employed due to its capacity to reduce perchlorate to harmless end-products. The employment of biodegradation was to reduce the concentration of perchlorate using batch reactors. In this study, an enrichment culture was used as the source of PRBs and also, elemental sulfur granules as the sole electron donor. Various parameters were considered to determine the optimum condition in which perchlorate is degraded by PRBs. Temperature, initial pH and initial perchlorate concentration were all varied and perchlorate concentration reduction, pH change and perchlorate removal eddiciency were recorded. A best condition parameter was also done in which all optimum conditions were gathered based on the previous parameters. Similar to previous studies, the inhibition effect of nitrate to perchlorate reduction was also studied. Various mole-to-mole relationships of the two anions were set to determine if inhibition is probable in a specific ratio. Kinetic parameter studies using the Monod model and the Monod inhibition model for nitrate inhibition parameter, were also done to assess the performance of the batch experiments. Results show that 35°C, pH 8.00 and 42.77 mgClO4-/L gave the highest perchlorate reduction rate. These values were considered as the optimum conditions. Also, nitrate was seen to inhibit perchlorate reduction on all mole-to-mole ratio. In summary, autotrophic perchlorate reduction using sulfur granules at optimum conditions can degrade perchlorate with the highest perchlorate reduction rate.
Thesis (Master of Science : Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Perchlorates; Nitrates; Water -- Purification -- Perchlorate removal